(untitled) (Research, Society and Development, 2022)
The objective was to compare the ribs in men, canines, horses and cattle, highlighting structural similarities in terms of functions, types, quantities and formats, using parts from the Human and Veterinary Anatomy Laboratory of the University of Franca, articles and books in this area of ​​expertise. Among the similar functions of the ribs, the support of the skeleton by participating in the formation of the rib cage, aid in respiratory movements and protection of organs stood out. As for the types, all species presented sternal ribs (articulating directly with the sternum) and sternal ribs (indirect contact with the sternum) in different amounts; on the other hand, only the canine and human, the floating ones (without connection with adjacent cartilage). The number of ribs corresponded to that of thoracic vertebrae, varying between species (13 pairs in the canine, 18 in the equine, 13 in the bovine and 12 in the human). Regarding the shape, there was variation according to each species, being longer, wider and flatter in cattle compared to horses; in canines more narrow and curved and in humans in semi-arches. It is possible to infer that, regardless of the species, the ribs perform the same functions, however, there are alternations in terms of types, quantities and formats, which may be involved with evolutionary and postural characteristics.